Uterine artery pulsatility and resistivity indices in pregnancy: Comparison of MRI and Doppler US. (July 2016) - Hawkes, R.A.; Patterson, A.J.; Priest, A.N.; Harrison, G.; Hunter, S.; Pinney, J.; Set, P.; Hilliard, N.; Graves, M.J.; Smith, G.C.S.; Lomas, D.J.
Abstract: Objective: The aim of this work was to evaluate whether the uterine arteries (UtA) could be identified and their flow profiles measured during a fetal MRI examination. A comparison was performed against same day sonographic Doppler assessment. Methods: 35 normal, healthy, singleton pregnancies at 28–32 weeks gestation underwent routine Doppler examination, followed by MRI examination. The resistivity index (RI) and pulsatility index (PI) of the left and right UtA were measured using phase contrast MRI. Bland Altman statistics were used to compare MRI and ultrasound results. Results: Sixty-nine comparable vessels were analysed. Six vessels were excluded due to artefact or technical error. Bland-Altman analysis demonstrated the ultrasound indices were comparable, although systematically lower than the MRI indices; Right UtA RI bias −0.03 (95% limits of agreement (LOA) −0.27 to +0.20), and left UtA RI bias −0.06 (95% LOA −0.26 to +0.14); Right UtA PI bias −0.06 (95% LOA −0.50 to +0.38), Left UtA PI bias −0.11 (95% LOA −0.54 to +0.32). The inter-rater agreement for the MRI derived PI and RI analysis was good. Conclusion: This study demonstrates that in the majority of early third trimester pregnancies, the uterine arteries can be identified, and their flow profiles measured using MRI, and that the derived PI and RI values are comparable with Doppler ultrasound values. Highlights: The majority of uterine arteries can be identified using MRI phase contrast methods. Uterine artery flow profiles can be measured using MRI phase contrast methods. Ultrasound indices were comparable, although systematically lower than MRI indices. The inter-rater agreement for the MRI derived PI and RI analysis was good.